Datasets design of gate diffusion input based pipeline architecture for numerically controlled oscillator - Ramana Reddy Gujjula; Chitra Perumal; Prakash Kodali; Bodapati Venkata Rajanna (Institute of Advanced Engineering and Science, 2022)
Gate diffusion input (GDI) is a technique, which enables reducing power consumption, area and delay in the digital circuits significantly, at the same time maintains low complexity of the logical design. This paper focuses on the analysis and interpretation of the design and implementation of GDI-based pipeline architecture for numerically controlled oscillator (NCO) using look up table (LUT). Based on the input signal and the alternate signal, this phase separation will separate the phase difference signal. The NCO generates a frequency and phase harmonized output signal with an antecedence fixed frequency clock. The 32-bit counter then compares the current count to the value stored in the compare register. Here the Coherent control comes into picture. It controls the carrier synchronizer by employing data from the 32-bit counter and the obtained data will be saved. It is updated and advanced using the third peer group of frequency synthesis technology. The test outcomes are accompanied with the theoretical concept and reproduced the results. The main objective of GDI-based pipeline architecture for NCO using LUT is to reduce the usage of metal oxide semiconductor field effect transistors (MOSFET’s). NCO is an indispensable component in many digital communication systems linked to modems, software-defined radios, and digital radio, digital down/upconverters for cellular and personal communications service base stations.